Asosiasi c.248 A>G gen CD1B dengan IgY dan Titer ND pada Ayam Sentul Galur Sensi-1 Agrinak - M. F. Al-Habib; S. Murtini; A. Gunawan; N. Ulupi; C. Sumantri (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
The aim of this study was to identify the polymorphism of the CD1B gene in c.248 in exon 3 and its association with IgY and ND titers in sentul chicken Sensi-1 Agrinak line. IgY is the main antibody of chickens while the ND titer is an ND specific antibody, both of which have an important role in the response of disease resistance. The Cluster of differentiation 1B (CD1B) gene is one of the major genes of disease resistance that functions in representing antigens through specific immune responses. This study used 17 sensi-1 chicken lines. The study was conducted by PCR sequencing method, ELISA test, and HI test. The result showed mutation on c248 A>G in exon 3. The SNP were polymorphic and Hardy Weinberg equilibrium. Thre were two A and G alleles and 3 genotypes namely AG, GG, and AA. The frequency of the GG genotype was higher (0.41) compared to other genotypes. The AG genotype were associated with IgY production and were not associated with ND titers.